Nikolai Mikhailovich Maliyev (to the 170 anniversary) - L. V. Saveliyeva; L. A. Grigoriyeva; R. V. Danilchuk; N. M. Melchikova (Бюллетень сибирской медицины, 2012)
Provided scientific biography of the founder of the Museum of human anatomy and the first Professor of normal Anatomy of the ImperialTomskUniversity N. Maliyev.